Molecular and morphological analyses of plants with ethnomedicinal uses in northeastern Peru - Tineo, Daniel; Calderon, Martha S.; Bustamante, Danilo E.; Oliva, Manuel (Ethnobotany Research and Applications, 2023)
Background: In Peru, ethnomedicinal plants have not been extensively assessed in the current context of DNA-based techniques. In the Amazonas region, medicinal plants use for diarrhea and fever treatment are mainly known by local or traditional names, while their phenotypic plasticity limits their proper morphological identification. Methods: In this regard, selected plants with ethnomedicinal uses in the Amazonas region were confirmed and characterized using morphology and multilocus phylogenies based on three molecular markers (ITS, matK, and rbcL). Results: This study reported four species with ethnomedicinal uses [Disciphania ernstii (Menispermaceae), Psidium fulvum (Myrtaceae), Styloceras penninervium (Buxaceae), Ugni myricoides (Myrtaceae)] distributed in humid forest, at 1,000–3,800 masl in the Amazonas region. The genetic markers that showed better resolution to distinguish species of the genera were ITS (Disciphania) and matK (Psidium, Ugni, and Styloceras). Conclusion: An initial screening regarding the diversity of plants with ethnomedicinal uses in the Amazonas region was needed and should include DNA-based techniques using these molecular markers to correctly identify them. This approach will facilitate further evaluation of the ancestral knowledge on the use of medicinal plants in Peru. Keywords: Amazonas, Buxaceae, DNA barcoding, ethnomedicine, Myrtaceae, Ranunculaceae